Assessment and Management of Dysphagia with Fiberoptic Endoscopic Examination of Swallowing (FESS) and its Future Implementation in Indonesia - Tamin, Susyana; Ku, Peter K; Cheung, Dilys (PERHATI-KL, 2004)
-